Genetic aspects of athletic performance: the African runners phenomenon - Vancini RL; Pesquero JB; Fachina RJ; Andrade MS; Borin JP; Montagner PC; de Lira CA (Dove Medical Press, 2014)
Rodrigo Luiz Vancini,1 João Bosco Pesquero,2 Rafael Júlio Fachina,3,4 Marília dos Santos Andrade,1 João Paulo Borin,3 Paulo César Montagner,3 Claudio Andre Barbosa de Lira51Centro de Educação Física e Desportos, Universidade Federal do Espírito Santo, Vitória, Espírito Santo, Brazil; 2Departamento de Biofísica, Universidade Federal de São Paulo, São Paulo, Brazil; 3Departamento de Ciência do Esporte, Faculdade de Educação Física, Universidade Estadual de Campinas, Campinas, Brazil; 4Confederação Brasileira de Basquetebol, Rio de Janeiro, Brazil; 5Setor de Fisiologia Humana e do Exercício, Faculdade de Educação Física, Universidade Federal de Goiás, Goiânia, BrazilAbstract: The current dominance of African runners in long-distance running is an intriguing phenomenon that highlights the close relationship between genetics and physical performance. Many factors in the interesting interaction between genotype and phenotype (eg, high cardiorespiratory fitness, higher hemoglobin concentration, good metabolic efficiency, muscle fiber composition, enzyme profile, diet, altitude training, and psychological aspects) have been proposed in the attempt to explain the extraordinary success of these runners. Increasing evidence shows that genetics may be a determining factor in physical and athletic performance. But, could this also be true for African long-distance runners? Based on this question, this brief review proposed the role of genetic factors (mitochondrial deoxyribonucleic acid, the Y chromosome, and the angiotensin-converting enzyme and the alpha-actinin-3 genes) in the amazing athletic performance observed in African runners, especially the Kenyans and Ethiopians, despite their environmental constraints.Keywords: genes, genotype, physical exercise, endurance runners